ANALISIS PENERAPAN PAJAK PENGHASILAN PASAL 21 PADA CV UNGGUL ABADI DI MANADO - Alfons, Winesthy Anasthazia Handaputri; Runtu, Treesje; Afandy, Dhullo (Universitas Sam Ratulangi, 2018)
Contribution of tax income year to year always shows a significant augmentation together with the augmentation of APBN for year to year. Tax is an important source of state’s income to run and to increase the national development for the people’s welfare and wealthy. The aim of this research is to analyse whether the application of determination, depositing and reporting of Income Tax Chapter 21 in CV Unggul Abadi in Manado has already met the rule of taxing. In this research the data used is qualificative, while the data source uses primary data and secondary data. The method of analyse used is descriptive analyse method. The result of the research concludes that determining, estimating, depositing and reporting Tax Income Chapter 21 in CV Unggul Abadi has not met the newest tax rule yet.Keywords: Tax Income Chapter 21, APBN, state’s income